ECTHR_COMMITTEE 25228/09 vom 5. Dezember 2017 , AFFAIRE BORȘAN c. ROUMANIE - Ecthr Committee (2017)
Violation de l'article 6 - Droit à un procès équitable (Article 6 - Procédure civile;Article 6-1 - Procès équitable); Violation: 6;6-1